Mimicked Periosteum Layer Based on Deposited Particle Silk Fibroin Membrane for Osteogenesis and Guided Bone Regeneration in Alveolar Cleft Surgery: Formation and in Vitro Testing. (2nd October 2021) - Moe, Yadanar Mya; Nuntanaranont, Thongchai; Khangkhamano, Matthana; Meesane, Jirut
ABSTRACT: An alveolar cleft is a critical tissue defect often treated with surgery. In this research, the mimicked periosteum layer based on deposited silk fibroin membrane was fabricated for guided bone regeneration in alveolar cleft surgery. The deposited silk fibroin particle membranes were fabricated by spray-drying with different concentrations of silk fibroin (v/v): 0.5% silk fibroin (0.5% SFM), 1% silk fibroin (1% SFM), 2% silk fibroin (2% SFM), and 1% silk fibroin film (1% SFF) as the control. The membranes were then characterized and the molecular organization, structure, and morphology were observed with FT-IR, DSC, and SEM. Their physical properties, mechanical properties, swelling, and degradation were tested. The membranes were cultured with osteoblast cells and their biological performance, cell viability and proliferation, total protein, ALP activity, and calcium deposition were evaluated. The results demonstrated that the membranes showed molecular transformation of random coils to beta sheets and stable structures. The membranes had a porous layer. Furthermore, they had more stress and strain, swelling, and degradation than the film. They had more unique cell viability and proliferation, total protein, ALP activity, calcium deposition than the film. The results of the study indicated that 1% SFM is promising for guided bone regeneration for alveolar cleft surgery.